A New Sustainable Hybrid Software Development Methodology: FIRAT-UG - Ulas, Mustafa; Guler, Hakan (Ieee, 2021)
Software development methods are one of the topics that many researchers have worked on. Methods such as Waterfall, Agile and Scrum are used to develop important software. All of these proposed methods are for software developers to produce manageable software during software development. However, it is important to ensure the continuity of human resources lossless and sustainable as well as managing software development phases. A new software development method is proposed in this study. With this method, the management of the software development phase will be a model in which human resources are managed integrated by participating in the work. With this model, it is aimed to minimize the potential risks of software development in this sector where is a lack of mobility and scarcity of human resource. The aim is to introduce a new sustainable software development methodology. This model was implemented under the coordination of F.U. Digital Transformation and Software Office and achieved successful results within 2 months. The model has reduced the human resources problems by %66.
9th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 28-29, 2021 -- Firat Univ, Elazig, TURKEY
Keywords: software architecture; software development; software development education